Women on the frontline: can a network provide a platform for activists in the volatile MENA region?. Issue 1 (2nd January 2017) - Michielsen, Dido
ABSTRACT: The article shares the experience of Women on the Frontline (WoF), a network of about 30 women's rights organisations with its origins in the Netherlands, and covering seven countries in the Middle East and North Africa (MENA) region. The organisations participating in WoF all have their own agendas and particular needs, but they share one common goal: sustainable peace in their country, with women and men playing an equally important role in the efforts to achieve this. This article relates how WoF was founded and how the organisation has had to adjust its goals since the Arab Uprisings. Progress made on women's rights has been challenged and it seems the clock has been turned back in the face of conflict and growing extremism, involving actors who draw on fundamentalist interpretations of religion to further their political aims. WoF is currently supporting the organisations to become stronger and get their stories heard internationally. Participating in a network can offer significant support in itself in challenging times.